Lithium iron manganese phosphate material, preparation method thereof, positive electrode sheet and secondary battery

CN117566713BActive Publication Date: 2026-10-09SHENZHEN DYNANONIC CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311339429.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2026-10-09
Estimated Expiration
2043-10-16

AI Technical Summary

Technical Problem

[0004]但是目前,磷酸锰铁锂材料的晶粒尺寸较大,导致磷酸锰铁锂材料容易出现极化作用,使得磷酸锰铁锂材料应用的二次电池的倍率性能和低温性能较差

Benefits of technology

[0044] According to the preparation method of this application, by adding a reducing organic solvent to provide a reducing atmosphere for the reaction system, the nucleation and growth of lithium manganese iron phosphate particles can be effectively controlled. Adding a capping agent can effectively inhibit further growth of the crystal nuclei, resulting in smaller crystal sizes and uniform particle size distribution of the lithium manganese iron phosphate particles, thereby shortening the lithium-ion transport path and improving the polarization of the material. Furthermore, since both the capping agent and the reducing organic solvent are organic materials, they can also serve as carbon sources, forming a carbon coating layer on the surface of the lithium manganese iron phosphate particles during calcination, thus improving the overall conductivity of the lithium manganese iron phosphate material. Therefore, the ionic conductivity and electronic conductivity of the lithium manganese iron phosphate material prepared by this application can be improved. When the lithium manganese iron phosphate material is used as a positive electrode active material in secondary batteries, it can effectively improve the electrochemical performance of the secondary battery, especially improving rate performance and low-temperature performance. Moreover, the preparation method of this application is simple, highly reproducible, and low-cost, making it suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117566713B_ABST
    Figure CN117566713B_ABST
Patent Text Reader

Abstract

The application provides a lithium iron manganese phosphate material, a preparation method thereof, a positive electrode sheet and a secondary battery. The preparation method comprises the following steps: adding a lithium source, an iron source, a manganese source, a phosphorus source and a capping agent into a reducing organic solvent and mixing to obtain a raw material system; placing the raw material system in a closed environment; heat treating the raw material system under stirring to make the raw material system generate a lithium iron manganese phosphate primary crystal system through a precipitation reaction; and calcining the lithium iron manganese phosphate primary crystal system under an inert atmosphere to form the lithium iron manganese phosphate material. The lithium iron manganese phosphate material comprises lithium iron manganese phosphate particles and a carbon coating layer arranged on at least part of the outer surface of the lithium iron manganese phosphate particles. When the lithium iron manganese phosphate material is applied to the secondary battery as a positive electrode active material, the rate performance and low-temperature performance of the secondary battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of lithium-ion battery material technology, specifically relating to a lithium manganese iron phosphate material and its preparation method, a positive electrode sheet, and a secondary battery. Background Technology

[0002] In recent years, due to the increasingly severe energy and environmental problems, vigorously developing new energy sources has become a consensus across society. With the rapid development of power batteries, rechargeable batteries have been widely used in electronic devices such as mobile phones, computers, and automobiles due to their advantages such as rapid and efficient energy conversion and storage, high energy density, long service life, and low self-discharge.

[0003] Secondary batteries typically include a positive electrode containing a positive electrode active material, and the performance of this material significantly impacts the battery's overall performance. Existing positive electrode active materials mainly include lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, and ternary materials. Lithium manganese iron phosphate is widely used due to its high discharge plateau and energy density, as well as excellent low-temperature performance.

[0004] However, currently, the large grain size of lithium manganese iron phosphate materials makes them prone to polarization, resulting in poor rate performance and low-temperature performance of secondary batteries using lithium manganese iron phosphate materials. Summary of the Invention

[0005] This application provides a lithium manganese iron phosphate material and its preparation method, a positive electrode sheet, and a secondary battery, which can improve the rate performance and low-temperature performance of the secondary battery.

[0006] In a first aspect, this application proposes a method for preparing lithium manganese iron phosphate material, the method comprising:

[0007] Lithium source, iron source, manganese source, phosphorus source and capping agent are added to a reducing organic solvent and mixed to form a raw material system;

[0008] Place the raw material system in a closed environment;

[0009] The raw material system was heat-treated under stirring conditions to induce a precipitation reaction and generate primary lithium manganese iron phosphate crystals.

[0010] The primary crystal system of lithium manganese iron phosphate is calcined in an inert atmosphere to form lithium manganese iron phosphate material, wherein the lithium manganese iron phosphate material includes lithium manganese iron phosphate particles and a carbon coating layer disposed on at least part of the outer surface of the lithium manganese iron phosphate particles.

[0011] In some embodiments, the capping agent includes at least one group selected from hydroxyl, carbonyl, and ether bonds.

[0012] In some embodiments, the lithium source includes at least one of inorganic lithium salts and organic lithium salts;

[0013] Optionally, the inorganic lithium salt includes at least one of lithium carbonate, lithium hydroxide, lithium nitrate, lithium silicate, lithium sulfate, lithium phosphate, lithium orthosilicate, lithium permanganate, lithium metaphosphate, lithium fluoride, lithium bromide, lithium oxide, lithium nitride, and lithium sulfide.

[0014] Optionally, the organic lithium salt includes at least one of lithium oxalate, lithium formate, lithium octanoate, lithium citrate, lithium salicylate, lithium trifluoroacetate, lithium acetoacetate, lithium difluorophosphate, lithium hexafluorophosphate, lithium benzoate, lithium pyruvate, lithium acetate, lithium methoxide, and lithium ethoxide.

[0015] In some embodiments, the iron source includes at least one of inorganic iron salts and organic iron salts;

[0016] Optionally, the inorganic iron salt includes at least one of ferrous nitrate, ferrous sulfide, ferrous sulfate, ferrous phosphate, ferrous iodide, ferrous fluoride, ferrous bromide and ferrous chloride;

[0017] Alternatively, the organic iron salt includes at least one of ferrous oxalate, ferrous acetylacetone, ferrous gluconate, and ferrous acetate.

[0018] In some embodiments, the manganese source includes at least one of inorganic manganese salts and organic manganese salts;

[0019] Optionally, the inorganic manganese salt includes at least one of manganese carbonate, manganese fluoride, manganese bromide, manganese chloride, manganese nitride, manganese carbide, manganese phosphide, manganese phosphate, manganese dihydrogen phosphate, manganese nitrate, manganese sulfate, manganese pyrophosphate, potassium permanganate, and potassium manganate.

[0020] Alternatively, the organic manganese salt includes at least one of manganese acetate, manganese oxalate, manganese pentacarbonyl, manganese decacarbonyl, manganese acetate, manganese acetylacetone, and manganese pyrophosphate.

[0021] In some embodiments, the phosphorus source includes at least one of sodium phosphorus salt, ammonium phosphorus salt, and potassium phosphorus salt;

[0022] Optionally, the sodium phosphate salt includes at least one of sodium pyrophosphate, sodium phosphite, sodium metaphosphate, sodium tripolyphosphate, and sodium hexafluorophosphate;

[0023] Optionally, the phosphate-containing ammonium salt includes at least one of ammonium hypophosphite, ammonium polyphosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium hexafluorophosphate, and ammonium phosphate;

[0024] Optionally, the phosphorus-containing potassium salt includes at least one of potassium hypophosphite, potassium pyrophosphate, tripotassium phosphate, potassium phosphite, potassium metaphosphate, and potassium hexafluorophosphate.

[0025] In some embodiments, the capping agent includes at least one selected from ascorbic acid, vitamin B, polyvinylpyrrolidone, citric acid, malic acid, and polyethylene glycol; and / or

[0026] Reducing organic solvents include reducing groups, which include at least one of amino, carbon-carbon double bond, carboxyl, thionyl, carbonyl and hydroxyl groups;

[0027] Optionally, the reducing organic solvent includes at least one of oleylamine, oleic acid, dimethyl sulfoxide, N-methylpyrrolidone, ethylene glycol, and glycerol.

[0028] In some embodiments, the molar ratio of the lithium source, the iron source, the manganese source, and the phosphorus source is 1:(0.1-0.9):(0.1-0.9):(0.8-1.2); and / or

[0029] Based on the total mass of the raw material system, the ratio of the mass percentage of lithium source to the mass percentage of capping agent is 1:(0.03~1.02).

[0030] In some embodiments, the preparation method also satisfies at least one of the following conditions:

[0031] (1) The heat treatment temperature is 100℃~200℃;

[0032] (2) The heat treatment time is 4h to 12h;

[0033] (3) The stirring speed of the stirring conditions is 5 rpm to 30 rpm;

[0034] (4) The calcination temperature is 500℃~700℃;

[0035] (5) The calcination time is 5h to 20h.

[0036] In some embodiments, after the step of heat-treating the raw material system under stirring conditions to induce a precipitation reaction and generate a primary lithium manganese iron phosphate crystal system, the method may further include:

[0037] Solid-liquid separation was performed on the primary crystal system of lithium manganese iron phosphate to separate the solid substances in the primary crystal system of lithium manganese iron phosphate.

[0038] The solid material undergoes cleaning and drying processes, among which...

[0039] The drying temperature is 60℃~90℃; and / or the drying time is 1h~24h.

[0040] Secondly, this application proposes a lithium manganese iron phosphate material, which includes lithium manganese iron phosphate particles and a carbon coating layer covering at least part of the surface of the lithium manganese iron phosphate particles, and the average particle size of the lithium manganese iron phosphate material is 5 nm to 15 nm.

[0041] In some embodiments, the carbon coating layer has a mass content of 0.5 wt% to 1.9 wt% relative to the total mass of the lithium manganese iron phosphate material.

[0042] Thirdly, this application proposes a positive electrode sheet, which includes a positive current collector and a positive active layer disposed on at least one side of the positive current collector. The positive active layer includes lithium manganese iron phosphate material obtained by the preparation method of any embodiment of the first aspect of this application or lithium manganese iron phosphate material as described in any embodiment of the second aspect of this application.

[0043] Fourthly, this application proposes a secondary battery, which includes a positive electrode as described in any embodiment of the third aspect of this application.

[0044] According to the preparation method of this application, by adding a reducing organic solvent to provide a reducing atmosphere for the reaction system, the nucleation and growth of lithium manganese iron phosphate particles can be effectively controlled. Adding a capping agent can effectively inhibit further growth of the crystal nuclei, resulting in smaller crystal sizes and uniform particle size distribution of the lithium manganese iron phosphate particles, thereby shortening the lithium-ion transport path and improving the polarization of the material. Furthermore, since both the capping agent and the reducing organic solvent are organic materials, they can also serve as carbon sources, forming a carbon coating layer on the surface of the lithium manganese iron phosphate particles during calcination, thus improving the overall conductivity of the lithium manganese iron phosphate material. Therefore, the ionic conductivity and electronic conductivity of the lithium manganese iron phosphate material prepared by this application can be improved. When the lithium manganese iron phosphate material is used as a positive electrode active material in secondary batteries, it can effectively improve the electrochemical performance of the secondary battery, especially improving rate performance and low-temperature performance. Moreover, the preparation method of this application is simple, highly reproducible, and low-cost, making it suitable for large-scale industrial production. Attached Figure Description

[0045] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.

[0046] Figure 1 This is a schematic diagram of the process for preparing lithium manganese iron phosphate material according to an embodiment of this application;

[0047] Figure 2This is a transmission electron microscope (TEM) image of the lithium manganese iron phosphate material in Example 1 of this application;

[0048] Figure 3 The X-ray diffraction (XRD) pattern of the lithium manganese iron phosphate material in Example 1 of this application;

[0049] Figure 4 The charge-discharge curves of the lithium-ion batteries using the lithium manganese iron phosphate materials of Example 1 and Comparative Example 1 at a rate of 0.1C are shown. Detailed Implementation

[0050] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the lithium manganese iron phosphate material, its preparation method, positive electrode sheet, and secondary battery of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0051] Preparation method of lithium manganese iron phosphate material

[0052] Firstly, this application proposes a method for preparing lithium manganese iron phosphate material.

[0053] like Figure 1 As shown, the preparation method includes:

[0054] Step S100: Add lithium source, iron source, manganese source, phosphorus source and capping agent to a reducing organic solvent and mix to form a raw material system;

[0055] Step S200: Place the raw material system in a closed environment;

[0056] Step S300: Heat-treat the raw material system under stirring conditions to induce a precipitation reaction and generate primary lithium manganese iron phosphate crystals.

[0057] Step S400: The primary crystal system of lithium manganese iron phosphate is calcined in an inert atmosphere to form lithium manganese iron phosphate material, wherein the lithium manganese iron phosphate material includes lithium manganese iron phosphate particles and a carbon coating layer disposed on at least part of the outer surface of the lithium manganese iron phosphate particles.

[0058] According to the preparation method of this application, by adding a reducing organic solvent to provide a reducing atmosphere for the reaction system, the nucleation and growth of lithium manganese iron phosphate particles can be effectively controlled. Adding a capping agent can effectively inhibit further growth of the crystal nuclei, resulting in smaller crystal sizes and uniform particle size distribution of the lithium manganese iron phosphate particles, thereby shortening the lithium-ion transport path and improving the polarization of the material. Furthermore, since both the capping agent and the reducing organic solvent are organic materials, they can serve as carbon sources, forming a carbon coating layer on the surface of the lithium manganese iron phosphate particles during calcination, thus improving the overall conductivity of the lithium manganese iron phosphate material. Therefore, the ionic conductivity and electronic conductivity of the lithium manganese iron phosphate material prepared by this application can be improved. When the lithium manganese iron phosphate material is used as a positive electrode active material in secondary batteries, it can effectively improve the electrochemical performance of the secondary battery, especially improving rate performance and low-temperature performance. Moreover, the preparation method of this application is simple, highly reproducible, and low-cost, making it suitable for large-scale industrial production.

[0059] [Step S100]

[0060] Step S100 provides each raw material and mixes them for a preliminary reaction; for example, lithium source, iron source, manganese source, phosphorus source and organic solvent are added to organic solvent according to a preset stoichiometric ratio, and stirred evenly to form a raw material system.

[0061] In some embodiments, the lithium source includes at least one of inorganic lithium salts and organic lithium salts. The aforementioned lithium source is readily available and readily reacts with other components.

[0062] For example, inorganic lithium salts include at least one of lithium carbonate, lithium hydroxide, lithium nitrate, lithium silicate, lithium sulfate, lithium phosphate, lithium orthosilicate, lithium permanganate, lithium metaphosphate, lithium fluoride, lithium bromide, lithium oxide, lithium nitride, and lithium sulfide.

[0063] For example, the organic lithium salt includes at least one of lithium oxalate, lithium formate, lithium octanoate, lithium citrate, lithium salicylate, lithium trifluoroacetate, lithium acetoacetate, lithium difluorophosphate, lithium hexafluorophosphate, lithium benzoate, lithium pyruvate, lithium acetate, lithium methoxide, and lithium ethoxide.

[0064] When a lithium source contains both lithium and phosphorus, the material can serve as both a lithium source and a phosphorus source.

[0065] In some embodiments, the iron source includes at least one of inorganic iron salts and organic iron salts. These iron sources are readily available and readily react with other components.

[0066] For example, inorganic iron salts include at least one of ferrous nitrate, ferrous sulfide, ferrous sulfate, ferrous phosphate, ferrous iodide, ferrous fluoride, ferrous bromide, and ferrous chloride.

[0067] For example, the organic iron salt includes at least one of ferrous oxalate, ferrous acetylacetone, ferrous gluconate, and ferrous acetate.

[0068] When an iron source contains both iron and phosphorus, the material can serve as both an iron source and a phosphorus source.

[0069] In some embodiments, the manganese source includes at least one of inorganic manganese salts and organic manganese salts. These manganese sources are readily available and readily react with other components.

[0070] For example, inorganic manganese salts include at least one of manganese carbonate, manganese fluoride, manganese bromide, manganese chloride, manganese nitride, manganese carbide, manganese phosphide, manganese phosphate, manganese dihydrogen phosphate, manganese nitrate, manganese sulfate, manganese pyrophosphate, potassium permanganate, and potassium manganate.

[0071] For example, the organic manganese salt includes at least one of manganese acetate, manganese oxalate, manganese pentacarbonyl, manganese decacarbonyl, manganese acetate, manganese acetylacetone, and manganese pyrophosphate.

[0072] When a manganese source contains both manganese and phosphorus, the material can serve as both a manganese and phosphorus source.

[0073] In some embodiments, the phosphorus source includes at least one of sodium phosphorus salt, ammonium phosphorus salt, and potassium phosphorus salt. These phosphorus sources are readily available and readily react with other components.

[0074] For example, the sodium phosphate salt includes at least one of sodium pyrophosphate, sodium phosphite, sodium metaphosphate, sodium tripolyphosphate, and sodium hexafluorophosphate.

[0075] For example, the phosphate-containing ammonium salt includes at least one of ammonium hypophosphite, ammonium polyphosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium hexafluorophosphate, and ammonium phosphate.

[0076] For example, the phosphorus-containing potassium salt includes at least one of potassium hypophosphite, potassium pyrophosphate, tripotassium phosphate, potassium phosphite, potassium metaphosphate, and potassium hexafluorophosphate.

[0077] The capping agent decomposes upon heating and can be adsorbed onto the crystal surface of lithium manganese iron phosphate compound to inhibit further crystal growth; and the capping agent can also act as a carbon source to form a carbon coating layer on the surface of lithium manganese iron phosphate particles.

[0078] In some embodiments, the capping agent includes at least one group selected from hydroxyl, carbonyl, and ether bonds.

[0079] For example, the capping agent includes at least one of ascorbic acid, vitamin B, polyvinylpyrrolidone, citric acid, malic acid, and polyethylene glycol.

[0080] In some embodiments, the reducing organic solvent includes a reducing group, which includes at least one selected from amino, carbon-carbon double bond, carboxyl, thionyl, carbonyl, and hydroxyl groups. The reducing solvent provides a reducing atmosphere for the system, which is beneficial for precipitating components in the raw material system to form a primary lithium manganese iron phosphate crystal system; it also promotes the nucleation and growth of lithium manganese iron phosphate; and serves as a carbon source to provide carbon coating for lithium manganese iron phosphate, improving the electrochemical performance of the material.

[0081] For example, the reducing organic solvent includes at least one of oleylamine, oleic acid, dimethyl sulfoxide, N-methylpyrrolidone, ethylene glycol, and glycerol.

[0082] In some implementations, the ratio of the mass content of the lithium source to the mass content of the reducing organic solvent is 1:(10-433) based on the total mass of the raw material system.

[0083] For example, the ratio of the mass content of the lithium source to the mass content of the reducing organic solvent can be 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, 1:55, 1:60, 1:65, 1:70, 1:75, 1:80, 1:85, 1:90, 1:95, 1:100, 1:105, 1:110, 1:120, 1:130, 1:140, 1:150, 1:160, 1:170, etc. 1:180, 1:190, 1:200, 1:210, 1:220, 1:230, 1:240, 1:250, 1:260, 1:270, 1:280, 1:290, 1:300, 1:310, 1:320, 1:330, 1:340, 1:350, 1:360, 1:370, 1:380, 1:390, 1:400, 1:410, 1:420, 1:430, 1:433, or a range consisting of any two of the above values.

[0084] In some embodiments, the molar ratio of lithium source, iron source, manganese source, and phosphorus source is 1:(0.1-0.9):(0.1-0.9):(0.8-1.2). When the molar ratio of lithium source, iron source, manganese source, and phosphorus source is within the above range, the desired primary crystal system of lithium manganese iron phosphate can be prepared, and the content of each element in the system is stable.

[0085] For example, the ratio of the molar amounts of lithium source, iron source, manganese source, and phosphorus source can be:

[0086] 1:(0.2~0.9):(0.1~0.9):(0.8~1.2), 1:(0.3~0.9):(0.1~0.9):(0.8~1.2), 1:(0.5~0.9):(0.1~0.9):(0.8~1.2), 1:(0.2~0.8):(0.1~0.9):(0.8~1.2), 1:(0.2~0.6):(0.1~0.9):(0.8~1.2), 1:(0.1~0.9):(0.2~0.9):(0.8~1.2), 1:(0.1~0.9):(0.3 ~0.9):(0.8~1.2), 1:(0.1~0.9):(0.5~0.9):(0.8~1.2), 1:(0.1~0.9):(0.2~0.8):(0.8~1.2), 1:(0.1~0.9):(0.2~0.6):(0.8~1.2), 1:(0.1~0.9):(0.1~0.9):(0.9~1.2), 1:(0.1~0.9):(0.1~0.9):(0.9~1.1) or 1:(0.1~0.9):(0.1~0.9):(0.9~1.0).

[0087] In some embodiments, the mass percentage ratio of lithium source to end-capping agent is 1:(0.03 to 1.02) based on the total mass of the raw material system. When the mass percentage ratio of lithium source to end-capping agent is within the above range, it is beneficial to form a carbon coating layer on the outer surface of the material, which can provide good protection for the material and improve electronic conductivity, thereby further mitigating the polarization of the material.

[0088] For example, the ratio of the mass percentage of lithium source to the mass percentage of capping agent can be 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.10, 1:0.11, 1:0.12, 1:0.15, 1:0.16, 1:0.17, 1:0.18, 1:0.20, or 1:0.22. 1:0.25, 1:0.30, 1:0.35, 1:0.40, 1:0.45, 1:0.50, 1:0.55, 1:0.60, 1:0.65, 1:0.70, 1:0.75, 1:0.80, 1:0.85, 1:0.90, 1:0.95, 1:1.00, 1:1.01, 1:1.02, or a range consisting of any two of the above values.

[0089] In some implementations, the raw material system may also include a dopant source, such as vanadium (V), titanium (Ti), nickel (Ni), chromium (chromium), magnesium (Mg), aluminum (Al), tin (Sn), etc. The dopant source can be an organic or inorganic substance corresponding to the dopant element. By incorporating dopant elements, the structural stability and electronic conductivity of lithium manganese iron phosphate materials can be further improved, thereby enhancing the electrochemical performance of the secondary battery.

[0090] [Step S200]

[0091] In step S200, the raw material system is placed in a closed environment, which can be a hydrothermal reactor or a pressure-resistant tube. The raw material system can be transferred to a closed environment such as a hydrothermal reactor or a pressure-resistant tube.

[0092] [Step S300]

[0093] In step S300, the raw material system is heat-treated under stirring conditions to induce a chemical precipitation reaction and generate a primary lithium manganese iron phosphate crystal system. For example, a closed environment, such as a hydrothermal reactor, is placed in an oil bath for heating. Stirring is continuously performed during the heating process in the oil bath. After a period of reaction, a primary lithium manganese iron phosphate crystal system containing a solid precipitate is obtained. This precipitate may appear as a black precipitate. The primary lithium manganese iron phosphate crystal system refers to a system in which lithium manganese iron phosphate crystals have already formed, but the crystallinity is relatively poor. The crystallinity and particle size can be further controlled through subsequent calcination processes.

[0094] By adjusting at least one of the heat treatment conditions and stirring conditions, the reaction rate and reaction time can be controlled, which is beneficial to obtaining the primary crystal system of lithium manganese iron phosphate with the required element content, and can reduce the risk of solid material agglomeration in the primary crystal system of lithium manganese iron phosphate, which is beneficial to the subsequent preparation of lithium manganese iron phosphate particles with smaller crystal grains.

[0095] In some embodiments, the heat treatment temperature can be 100°C to 200°C. For example, the heat treatment temperature can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, or a range of any two of the above values.

[0096] In some embodiments, the heat treatment time can be from 4 hours to 12 hours. For example, the heat treatment time can be 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, 10.5 hours, 11 hours, 11.5 hours, 12 hours, or any range of two of the above values.

[0097] In some embodiments, the stirring rate of the stirring conditions is 5 rpm to 30 rpm. For example, the stirring rate of the stirring conditions can be 5 rpm, 6 rpm, 7 rpm, 8 rpm, 9 rpm, 10 rpm, 11 rpm, 12 rpm, 13 rpm, 14 rpm, 15 rpm, 16 rpm, 17 rpm, 18 rpm, 19 rpm, 20 rpm, 21 rpm, 22 rpm, 23 rpm, 24 rpm, 25 rpm, 26 rpm, 27 rpm, 28 rpm, 29 rpm, 30 rpm, or a range of any two of the above values.

[0098] [Step S400]

[0099] In step S400, the primary lithium manganese iron phosphate system is calcined under an inert atmosphere to form lithium manganese iron phosphate material. The lithium manganese iron phosphate material includes lithium manganese iron phosphate particles and a carbon coating layer disposed on at least a portion of the outer surface of the lithium manganese iron phosphate particles. After calcination, the primary lithium manganese iron phosphate system forms fine-grained particles. The capping agent and reducing organic solvent, through the calcination process, form the carbon coating layer, which further enhances the material's stability and electrochemical stability.

[0100] In some implementations, the inert atmosphere may be argon (Ar) or nitrogen (N2).

[0101] In some embodiments, the calcination temperature is 500°C to 700°C. Exemplarily, the calcination temperature can be 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, or a range of any two of the above values.

[0102] In some embodiments, the calcination time is 5h to 20h. For example, the calcination time can be 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h or any range of two of the above values.

[0103] By adopting the above calcination conditions, the rate and extent of crystal growth in the primary crystal system of lithium manganese iron phosphate can be adjusted, which is beneficial to obtaining lithium manganese iron phosphate materials with smaller size.

[0104] [Step S500]

[0105] In some embodiments, after step S300, the preparation method described in this application may further include step S500, which may include:

[0106] Solid-liquid separation was performed on the primary crystal system of lithium manganese iron phosphate to separate the solid material of the primary crystal system of lithium manganese iron phosphate.

[0107] The solid material is cleaned and dried.

[0108] The lithium manganese iron phosphate primary crystal system prepared in step S300 may include solid and liquid substances. The solid substance is mainly lithium manganese iron phosphate primary crystals, and the liquid substance may be unreacted raw materials or organic solvents. The solid substance in the lithium manganese iron phosphate primary crystal system is separated, cleaned, and dried in preparation for subsequent calcination. In this embodiment, centrifugation can be used for the separation and cleaning of the solid substance. The liquid used for centrifugation can be at least one of anhydrous ethanol, isopropanol, and acetone.

[0109] In some embodiments, the drying temperature is 60°C to 90°C. Exemplarily, the drying temperature can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, or a range of any two of the above values.

[0110] In some embodiments, the drying time is 1 hour to 24 hours. For example, the drying time can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, or a range of any two of the above values.

[0111] Lithium manganese iron phosphate materials

[0112] Secondly, this application also provides a lithium manganese iron phosphate material, which includes lithium manganese iron phosphate particles and a carbon coating layer covering at least a portion of the surface of the lithium manganese iron phosphate particles, wherein the average particle size of the lithium manganese iron phosphate particles is 5 nm to 15 nm. The lithium manganese iron phosphate material in the embodiments of this application can be prepared by the preparation method of any embodiment of the first aspect of this application, or it can be prepared using equipment and methods known in the art.

[0113] The relatively small average particle size of lithium manganese iron phosphate particles results in a smaller overall particle size of the lithium manganese iron phosphate material, which helps to shorten the lithium ion transport path and thus improve the polarization of the material. When lithium manganese iron phosphate is used as a positive electrode active material in secondary batteries, it can effectively improve its electrochemical performance, especially its rate performance and low-temperature performance.

[0114] For example, the average particle size of lithium manganese iron phosphate particles can be 5nm, 5.5nm, 6nm, 6.5nm, 7nm, 7.5nm, 8nm, 8.5nm, 8.9nm, 9nm, 9.5nm, 9.7nm, 10nm, 10.5nm, 11nm, 11.5nm, 12nm, 12.5nm, 12.6nm, 13nm, 13.5nm, 14nm, 14.1nm, 14.5nm, 15nm, or any range of two of the above values.

[0115] In some embodiments, the carbon coating layer has a mass content of 0.5 wt% to 1.9 wt% relative to the total mass of the lithium manganese iron phosphate material. The carbon coating layer provides good protection for the material and improves electronic conductivity, which helps to further mitigate the polarization of the material.

[0116] For example, the mass content of the carbon coating layer can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.88wt%, 0.9wt%, 0.95wt%, 1.0wt%, 1.03wt%, 1.1wt%, 1.12wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.53wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, or any range of two of the above values.

[0117] Positive electrode sheet

[0118] Thirdly, embodiments of this application provide a positive electrode sheet, the positive electrode sheet including a positive current collector and a positive active layer disposed on at least one side of the positive current collector, the positive active layer including a positive active material, the positive active material including lithium manganese iron phosphate material as in any embodiment of the second aspect of this application.

[0119] In the positive electrode of this application embodiment, the lithium iron phosphate particles of the lithium manganese phosphate material have a small grain size, resulting in a shorter lithium ion transport path. Furthermore, the surface of the lithium iron phosphate particles is coated with a carbon coating layer, which can improve the overall conductivity of the lithium iron phosphate material. Therefore, when the positive electrode is applied to a secondary battery, it can effectively improve the electrochemical performance of the secondary battery, especially the rate performance and low-temperature performance.

[0120] The mass content of lithium manganese iron phosphate material in the positive electrode active layer can be designed according to battery performance requirements. For example, in one embodiment, based on the total mass of the positive electrode active layer, the mass content of lithium manganese iron phosphate material can be controlled to be 85wt% to 95wt%. Lithium manganese iron phosphate material within this range can endow the positive electrode with higher capacity and better electrochemical performance, thereby improving the energy density, rate performance and low-temperature performance of the secondary battery.

[0121] Of course, the positive electrode active layer may also contain one or more of the following electrode active materials: lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxide phosphate, lithium fluorinated vanadium phosphate, lithium titanate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.

[0122] In one embodiment, the positive electrode active layer may further contain at least one of a binder and a conductive agent. The binder may be a commonly used electrode binder, such as one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan, and chitosan derivatives. The conductive agent may be a commonly used conductive agent, such as one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60, and carbon nanotubes.

[0123] In some embodiments, the positive current collector can be a metal film layer or a composite layer. The metal film layer can be aluminum foil or an alloy composed of aluminum and other metal elements, such as aluminum-copper alloy or aluminum-nickel alloy. The composite layer can be a composite structure composed of an organic polymer layer and a metal layer. For example, the composite layer includes an organic polymer layer, a metal layer, and an organic polymer layer arranged sequentially in the thickness direction. The organic polymer layer includes polyethylene terephthalate (PET).

[0124] In some embodiments, the preparation process of the positive electrode sheet can be as follows: mixing positive active material, conductive agent and binder to obtain positive electrode slurry, coating the positive electrode slurry on positive current collector, and preparing the positive electrode sheet through steps such as drying, rolling and die cutting.

[0125] Secondary batteries

[0126] Fourthly, this application also provides a secondary battery. The secondary battery of this application includes a positive electrode, which is a positive electrode as described in any embodiment of the third aspect of this application. In the positive electrode of this application, the lithium iron phosphate particles of the lithium manganese phosphate material have a small grain size, resulting in a shorter lithium-ion transport path. Furthermore, the surface of the lithium manganese iron phosphate particles is coated with a carbon coating layer, which can improve the overall conductivity of the positive electrode active material, thereby effectively improving the electrochemical performance of the secondary battery, especially its rate performance and low-temperature performance.

[0127] In some embodiments, the secondary battery may also include a negative electrode sheet, which may be a negative electrode sheet commonly used in the art. For example, the negative electrode sheet may include a negative current collector and a negative active layer. The negative current collector may be made of copper foil, and the negative active layer may be made of graphite, etc.

[0128] In some embodiments, the secondary battery may also include a separator membrane, which may be an organic polymer membrane layer, such as a polypropylene membrane layer or a polyethylene membrane layer.

[0129] In some embodiments, the secondary battery may also include an electrolyte, which may be a commonly used electrolyte in the art, such as lithium hexafluorophosphate as the lithium salt.

[0130] The present application will now be described in conjunction with specific embodiments.

[0131] Preparation of Lithium Manganese Iron Phosphate Materials in Examples and Comparative Cases

[0132] Example 1

[0133] A method for preparing lithium manganese iron phosphate material, the specific steps of which are as follows:

[0134] (1) 305 mg lithium carbonate, 238 mg ferrous sulfate, 285 mg manganese carbonate, 479 mg ammonium dihydrogen phosphate and 90 mg ascorbic acid capping agent were added to a polytetrafluoroethylene hydrothermal reactor containing 50 mL organic solvent oleamine and stirred for 1 h to form a uniform emulsion raw material system.

[0135] After tightening the hydrothermal reactor, it was placed in an oil bath for heat treatment. The heat treatment temperature was 150℃ and the heat treatment time was 10h. During the heat treatment, the solution in the hydrothermal reactor was kept under stirring at a stirring rate of 15rpm to obtain the primary crystal system of lithium manganese iron phosphate.

[0136] (2) After the reaction in step (1) is completed, the mixture is cooled naturally. Then, the primary crystal system of lithium manganese iron phosphate is centrifuged to separate the precipitate. After repeatedly rinsing the precipitate with 1000 mL of anhydrous ethanol, it is placed in a vacuum drying oven at 80°C for 12 hours.

[0137] The dried powder was then transferred to a tube furnace and calcined at high temperature in a protected atmosphere of N2. The calcination temperature was 700℃ and the calcination time was 8h to obtain lithium manganese iron phosphate material.

[0138] Example 2

[0139] A method for preparing lithium manganese iron phosphate material, the specific steps of which are as follows:

[0140] (1) 305 mg lithium carbonate, 238 mg ferrous oxalate, 312 mg manganese chloride, 479 mg ammonium dihydrogen phosphate and 67 mg capping agent citric acid were added to a polytetrafluoroethylene hydrothermal reactor containing 50 mL organic solvent oleylamine and stirred for 1 h to form a uniform emulsion raw material system.

[0141] After tightening the hydrothermal reactor, it was placed in an oil bath for heat treatment. The heat treatment temperature was 140℃ and the heat treatment time was 12h. During the heat treatment, the solution in the hydrothermal reactor was kept under stirring at a stirring rate of 20rpm to obtain the primary crystal system of lithium manganese iron phosphate.

[0142] (2) After the reaction in step (1) is completed, the mixture is allowed to cool naturally. Then, the primary crystal system of lithium manganese iron phosphate is centrifuged to separate the precipitate. After repeatedly rinsing the precipitate with 1000 mL of acetone, it is placed in a vacuum drying oven at a drying temperature of 70°C for 10 hours.

[0143] The dried powder was then transferred to a tube furnace and calcined at high temperature in a protected atmosphere of N2. The calcination temperature was 700℃ and the calcination time was 6h to obtain lithium manganese iron phosphate material.

[0144] Example 3

[0145] A method for preparing lithium manganese iron phosphate material, the specific steps of which are as follows:

[0146] (1) 150 mg lithium hydroxide, 361 mg ferrous oxalate, 450 mg manganese carbonate, 860 mg diammonium hydrogen phosphate and 50 mg capping agent citric acid were added to a polytetrafluoroethylene hydrothermal reactor containing 50 mL organic solvent oleamine and stirred for 1 h to form a uniform emulsion raw material system.

[0147] After tightening the hydrothermal reactor, it was placed in an oil bath for heat treatment. The heat treatment temperature was 120℃ and the heat treatment time was 12h. During the heat treatment, the solution in the hydrothermal reactor was kept under stirring at a stirring rate of 20rpm to obtain the primary crystal system of lithium manganese iron phosphate.

[0148] (2) After the reaction in step (1) is completed, the mixture is allowed to cool naturally. Then, the primary crystallization system of lithium manganese iron phosphate is centrifuged to separate the precipitate. After repeatedly rinsing the precipitate with 1000 mL of isopropanol, it is placed in a vacuum drying oven at a drying temperature of 90°C for 8 hours.

[0149] The dried powder was then transferred to a tube furnace and calcined at high temperature in a protected atmosphere of N2 at 600°C for 10 hours to obtain lithium manganese iron phosphate material.

[0150] Example 4

[0151] A method for preparing lithium manganese iron phosphate material, the specific steps of which are as follows:

[0152] (1) Add 305mg lithium carbonate, 209mg ferrous chloride, 285mg manganese carbonate, 479mg ammonium dihydrogen phosphate, and 60mg vitamin B capping agent to a polytetrafluoroethylene hydrothermal reactor containing 50mL organic solvent oleylamine, and stir for 1h to form a uniform emulsion raw material system.

[0153] After tightening the hydrothermal reactor, it was placed in an oil bath for heat treatment. The heat treatment temperature was 140℃ and the heat treatment time was 12h. During the heat treatment, the solution in the hydrothermal reactor was kept under stirring at a stirring rate of 30rpm to obtain the primary crystal system of lithium manganese iron phosphate.

[0154] (2) After the reaction in step (1) is completed, the mixture is cooled naturally. Then, the primary crystal system of lithium manganese iron phosphate is centrifuged to separate the precipitate. After repeatedly rinsing the precipitate with 1000 mL of anhydrous ethanol, it is placed in a vacuum drying oven at a drying temperature of 70°C for 12 hours.

[0155] The dried powder was then transferred to a tube furnace and calcined at high temperature in a protected atmosphere of N2 at 550°C for 12 hours to obtain lithium manganese iron phosphate material.

[0156] Example 5

[0157] A method for preparing lithium manganese iron phosphate material, the specific steps of which are as follows:

[0158] (1) Add 100mg lithium hydroxide, 254mg ferrous sulfate, 289mg manganese carbonate, 460mg ammonium dihydrogen phosphate and 100mg malic acid capping agent to a polytetrafluoroethylene hydrothermal reactor containing 50mL organic solvent ethylene glycol, and stir for 1h to form a uniform emulsion raw material system.

[0159] After tightening the hydrothermal reactor, it was placed in an oil bath for heat treatment. The heat treatment temperature was 180℃ and the heat treatment time was 6h. During the heat treatment, the solution in the hydrothermal reactor was kept under stirring at a stirring rate of 25rpm to obtain the primary crystal system of lithium manganese iron phosphate.

[0160] (2) After the reaction in step (1) is completed, the mixture is allowed to cool naturally. Then, the primary crystal system of lithium manganese iron phosphate is centrifuged to separate the precipitate. After repeatedly rinsing the precipitate with 1000 mL of isopropanol, it is placed in a vacuum drying oven at a drying temperature of 70°C for 10 hours.

[0161] The dried powder was then transferred to a tube furnace and calcined at high temperature in a protected atmosphere of N2. The calcination temperature was 700℃ and the calcination time was 10h to obtain lithium manganese iron phosphate material.

[0162] Comparative Example 1

[0163] A method for preparing lithium manganese iron phosphate material, the specific steps of which are as follows:

[0164] (1) Mix 2.0g lithium carbonate, 1.5g ferrous oxalate, 1.8g manganese carbonate, 3.1g ammonium dihydrogen phosphate, 0.2g ascorbic acid and 40mL anhydrous ethanol and then ball mill them at 300rpm for 4h.

[0165] After ball milling, the product was placed in a vacuum drying oven at 80°C for 12 hours.

[0166] The dried powder was placed in a tube furnace and calcined at high temperature in a protective atmosphere of N2. The calcination temperature was 700℃ and the calcination time was 8h.

[0167] (2) After grinding the dried product in (1), it is placed in a tube furnace and calcined at high temperature in a protected atmosphere of N2. The calcination temperature is 700℃ and the calcination time is 8h to obtain lithium manganese iron phosphate material.

[0168] Comparative Example 2

[0169] Lithium manganese iron phosphate material was prepared using a similar preparation method as in Example 1. The difference from Example 1 is that the organic solvent "50 mL oleylamine" in Comparative Example 2 was replaced with "50 mL deionized water".

[0170] The positive electrode active material prepared using this method has a large particle size, uneven particle size distribution, and poor morphological regularity.

[0171] Comparative Example 3

[0172] Lithium manganese iron phosphate material was prepared using a similar preparation method to Example 1. The difference from Example 1 is that no capping agent was added in Comparative Example 3.

[0173] The positive electrode active material prepared using this method has a large particle size, uneven particle size distribution, and poor morphological regularity.

[0174] Preparation of Lithium-ion Batteries in Examples and Comparative Cases

[0175] 1. Preparation of positive electrode sheet

[0176] (1) Preparation of positive electrode slurry: The positive electrode active material, superconducting carbon black (SP) and binder polyvinylidene fluoride (PVDF) were added to an agate ball mill jar at a mass ratio of 90:5:5, and then the solvent N-methylpyrrolidone (NMP) was added and ball milled to mix them into a positive electrode slurry; the lithium manganese iron phosphate materials prepared in the above examples and comparative examples were used as positive electrode active materials for lithium-ion batteries.

[0177] (2) Coating of positive electrode slurry: Adjust the scale of the scraper of the coating machine, and evenly coat the ball-milled positive electrode slurry onto the aluminum foil. Place the coated electrode in a vacuum drying oven for baking, cold pressing and stamping to obtain the positive electrode.

[0178] 2. Preparation of lithium-ion batteries

[0179] In a glove box, the negative electrode shell, spring sheet, steel sheet, lithium sheet, separator, positive electrode sheet, and positive electrode shell are assembled in sequence. During the process, 10 μL of electrolyte (lithium salt including 1 mol / L lithium hexafluorophosphate LiPF6, and organic solvent including ethylene carbonate EC and dimethyl carbonate DMC (volume ratio 1:1)) is injected. Then, the button cell is sealed using a sealing machine to obtain lithium-ion batteries.

[0180] The relevant parameters for the embodiments and comparative examples are shown in Tables 1 and 2.

[0181] Performance testing

[0182] 1. Morphological characterization of lithium manganese iron phosphate materials

[0183] The lithium manganese iron phosphate materials prepared in the examples and comparative examples were tested using transmission electron microscopy (TEM). Figure 2 The TEM image of the positive electrode active material in Example 1 is shown. Figure 2 As can be seen from a and 2b, the product obtained in Example 1 has uniform and fine particles with a uniform particle size distribution. The average particle size range is only 5nm to 15nm, and the dispersion is good with no serious agglomeration.

[0184] 2. X-ray diffraction (XRD) analysis of lithium manganese iron phosphate materials

[0185] The lithium manganese iron phosphate materials prepared in the examples and comparative examples were analyzed by XRD. Figure 3 The XRD pattern of the positive electrode active material in Example 1 is shown. The product of Example 1 is a typical lithium manganese iron phosphate phase. The XRD diffraction peak pattern is in perfect agreement with the standard PDF card #13-0336 of lithium manganese iron phosphate, thus verifying that the product of Example 1 contains lithium manganese iron phosphate.

[0186] 3. Performance Characterization of Lithium-ion Batteries

[0187] The electrochemical performance of the examples and comparative examples was characterized by the relevant performance tests shown in Table 2 below. The test conditions were determined according to industry standard test methods.

[0188] Test Results

[0189] The test results are shown in Tables 1 and 2.

[0190] Table 1. Physical parameters of lithium manganese iron phosphate materials in the examples and comparative examples

[0191]

[0192] Table 2. Electrochemical performance of lithium-ion batteries in the examples and comparative examples

[0193]

[0194] Depend on Figure 4 As shown in Table 2,

[0195] Comparative Example 1: The lithium manganese iron phosphate material synthesized by the traditional solid-state method has a large particle size and does not have an ultra-small particle morphology. Its discharge specific capacity at 0.1C rate is only 139.8 mAh / g, and its discharge specific capacity at 5C rate is only 90.2 mAh / g. However, its discharge specific capacity at 1C rate under low temperature conditions of -20℃ is as high as 65.8 mAh / g.

[0196] The lithium manganese iron phosphate materials prepared in Examples 1-5 of this application exhibit ultra-small particle morphology, thus demonstrating excellent electrochemical performance. In particular, the product of Example 1 shows a discharge specific capacity as high as 160.4 mAh / g at 0.1C rate, 136.7 mAh / g at 5C rate, and a discharge specific capacity as high as 105.6 mAh / g at 1C rate under low temperature conditions of -20℃. Furthermore, the resistivity of the lithium manganese iron phosphate materials in these examples ranges from 10 Ω·cm to 20.4 Ω·cm.

[0197] Therefore, it can be seen that the smaller particle size of the lithium manganese iron phosphate material in the embodiments of this application can effectively improve the electrochemical performance of the secondary battery, especially the rate performance and low-temperature discharge performance.

[0198] Although Comparative Example 2 uses a similar method to that of this application to prepare lithium manganese iron phosphate material, its solvent is deionized water, which easily generates larger-grained lithium manganese iron phosphate particles, resulting in a larger overall average particle size of the lithium manganese iron phosphate material. Although the electrochemical performance of the secondary battery is slightly improved compared to Comparative Example 1, it cannot effectively improve the electrochemical performance of the secondary battery.

[0199] Comparative Example 3 did not use a capping agent, which easily resulted in the formation of larger-grained lithium manganese iron phosphate particles, leading to a larger overall average particle size of the lithium manganese iron phosphate material. Although the electrochemical performance of the secondary battery was slightly improved compared to Comparative Example 1, it could not effectively improve the electrochemical performance of the secondary battery.

[0200] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limiting the present application, and that changes, substitutions and modifications can be made to the embodiments without departing from the spirit, principles and scope of the present application.

Claims

1. A method for preparing lithium manganese iron phosphate material, characterized in that, include: Lithium source, iron source, manganese source, phosphorus source and capping agent are added to a reducing organic solvent and mixed to form a raw material system; Place the raw material system in a closed environment; The raw material system is heat-treated under stirring conditions to induce a precipitation reaction and generate a primary lithium manganese iron phosphate crystal system; the heat treatment temperature is 100℃~150℃. The primary crystal system of lithium manganese iron phosphate is calcined under an inert atmosphere to form lithium manganese iron phosphate material, wherein the lithium manganese iron phosphate material includes lithium manganese iron phosphate particles and a carbon coating layer disposed on at least a portion of the outer surface of the lithium manganese iron phosphate particles. Based on the total mass of the raw material system, the ratio of the mass percentage of the lithium source to the mass percentage of the capping agent is 1:(0.03~1.02). The average particle size of the lithium manganese iron phosphate material is 5nm~15nm; The capping agent includes at least one of ascorbic acid, vitamin B, polyvinylpyrrolidone, citric acid, malic acid, and polyethylene glycol; The reducing organic solvent includes at least one of oleylamine, oleic acid, dimethyl sulfoxide, N-methylpyrrolidone, ethylene glycol, and glycerol.

2. The preparation method according to claim 1, characterized in that, The ratio of the molar amounts of the lithium source, the iron source, the manganese source, and the phosphorus source is 1:(0.1~0.9):(0.1~0.9):(0.8~1.2).

3. The preparation method according to claim 1, characterized in that, The preparation method also satisfies at least one of the following conditions. (1) The heat treatment time is 4h~12h; (2) The stirring rate under the stirring conditions is 5 rpm to 30 rpm; (3) The calcination temperature is 500℃~700℃; (4) The calcination time is 5h~20h.

4. The preparation method according to claim 1, characterized in that, After the step of heat-treating the raw material system under stirring conditions to induce a precipitation reaction and generate a primary lithium manganese iron phosphate crystal system, the method further includes: The primary crystal system of lithium manganese iron phosphate is subjected to solid-liquid separation to separate the solid substances in the primary crystal system of lithium manganese iron phosphate. The solid material is then cleaned and dried, wherein... The drying temperature is 60℃~90℃; and / or the drying time is 1h~24h.

5. A lithium manganese iron phosphate material prepared by the preparation method according to any one of claims 1 to 4, characterized in that, It includes lithium manganese iron phosphate particles and a carbon coating layer covering at least a portion of the surface of the lithium manganese iron phosphate particles, wherein the average particle size of the lithium manganese iron phosphate material is 5 nm to 15 nm.

6. The lithium manganese iron phosphate material according to claim 5, characterized in that, The carbon coating layer has a mass content of 0.5wt% to 1.9wt% relative to the total mass of the lithium manganese iron phosphate material.

7. A positive electrode sheet, characterized in that, It includes a positive current collector and a positive active layer disposed on at least one side of the positive current collector, wherein the positive active layer includes the lithium manganese iron phosphate material as described in claim 5 or 6.

8. A secondary battery, characterized in that, Includes the positive electrode sheet as described in claim 7.

Citation Information

Patent Citations

  • Preparation method of lithium ion phosphate / carbon composite material for high-rate-capability lithium ion battery

    CN103427079A

  • Lithium iron manganese phosphate cathode active material and method for producing the same

    JP5890886B1

  • Method for Preparing Lithium Manganese Iron Phosphate and Product of Olivine Type Obtained from the Same

    KR1020160080243A